Measurement of suction and volume change behaviour of unsaturated soils - Sri Widiastuti (2008)
Soil suction is the key factor to understanding the behaviour of unsaturated soils. Soil suction or total suction consists of matric suction and osmotic suction. Both components are important to unsaturated soil mechanics. The total, matricand osmotic suctions of a soil specimen can be measured independently in the laboratory using different techniques. However, it is rare to measure total, matric and osmotic suctions for a single soil specimen. Generally, the total or matric suction is measured and the osmotic suction is inferred from the difference between total and matric suction. The accuracies in the measurement of the different suction components are different.